087 The effect of antihypertensive treatment on headache and blood pressure variability in randomised controlled trials: a systematic review. Issue 3 (9th February 2012) - Webb, A; Rothwell, P M
Abstract : Introduction: Antihypertensive drugs reduce headache but differences between drug-classes are unclear. Any differences may be due to class-effects on cerebrovascular tone and hence stroke risk and might correlate with class-effects on peripheral vascular tone and hence blood pressure variability (BPV). Methods: In a systematic review of antihypertensive class effects on BPV and headache in randomised controlled trials, we determined pooled drug-class effects on group BPV (variance ratio-VR) and on headache (reported as adverse effects) by random-effects meta-analysis. Results: Antihypertensive drugs reduced headache compared to placebo (OR=0.75, 95% CI 0.69 to 0.82, p<0.0001, 43 672 patients). Effects on headache varied (heterogeneity-p=0.0007), being reduced most by β-blockers (vs placebo 0.49, 0.33 to 0.68, p<0.0001, 1916 pts, 16 trials; vs other classes OR=0.73, 0.62 to 0.85, p=0.0002, 7844 pts, 49 trls) and increased by calcium channel blockers (vs placebo OR=0.95, 0.79 to 1.15, 9291 pts, 65 trls; vs other classes OR=1.19, 1.05 to 1.35, p=0.009, 42 732 pts, 101 trls). These effects on headache were opposite to effects on BPV (CCBs: VR=0.81, 0.71 to 0.85, p<0.0001; β-blocker VR=1.17, 1.07 to 1.28, p<0.0001), but were unrelated to mean SBP. Conclusions: Antihypertensive drug-classes differ in their effects on headache in a manner that could be explained by effects on vascular tone; vasodilators increasing headache and decreasing BPV and vasoconstrictors decreasing headache but increasing BPV.